2006
DOI: 10.1161/01.res.0000218454.76784.66
|View full text |Cite
|
Sign up to set email alerts
|

Postinfarct Cytokine Therapy Regenerates Cardiac Tissue and Improves Left Ventricular Function

Abstract: Abstract-We systematically investigated the comparative efficacy of three different cytokine regimens, administered after a reperfused myocardial infarction, in regenerating cardiac tissue and improving left ventricular (LV) function. Wild-type (WT) mice underwent a 30-minute coronary occlusion followed by reperfusion and received vehicle, granulocyte colony-stimulating factor (G-CSF)ϩFlt-3 ligand (FL), G-CSFϩstem cell factor (SCF), or G-CSF alone starting 4 hours after reperfusion. In separate experiments, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 27 publications
2
102
0
Order By: Relevance
“…BM-derived cells (BMCs) have been shown to participate in tissue repair following injury to several organs, including the brain, liver, lung, kidney [1][2][3][4][5] as well as the heart [6][7][8][9][10][11]. Cardiomyocytes derived from BMCs have been noted in the heart after myocardial infarction (MI) [6,7,10]. The egress of primitive cells from the BM into the blood is an essential first step for effective tissue repair by BMCs [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…BM-derived cells (BMCs) have been shown to participate in tissue repair following injury to several organs, including the brain, liver, lung, kidney [1][2][3][4][5] as well as the heart [6][7][8][9][10][11]. Cardiomyocytes derived from BMCs have been noted in the heart after myocardial infarction (MI) [6,7,10]. The egress of primitive cells from the BM into the blood is an essential first step for effective tissue repair by BMCs [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The regenerated/newly formed blood vessels, especially after F/S/G treatment, were partly bone marrow-derived, as indicated by the capillary coexpression of CD31 and eGFP. This is the first time such an observation has been reported in irradiated vessels, although it has been shown to occur after ischemia in arterioles and capillaries of the limb (48,49) and the infarcted heart (27,31). The more pronounced improvement of the vasculature after F/S/G treatment may be due to an enhanced mobilization of endothelial progenitor cells, which are not only capable of differentiating into endothelial cells (50) but can also release growth factors that act in a paracrine way to support the endothelium (51).…”
Section: Discussionmentioning
confidence: 70%
“…Radiation-induced damage to the vasculature will cause secondary damage to the tissue. Because G-CSF alone or in combination with Flt-3L or SCF has been shown to promote the formation of blood vessels after myocardial infarct (27), the vascular structure of irradiated glands was investigated. Microscopic comparison of the vasculature of glands of all groups, visualized by CD31 staining, immediately indicated differences in blood vessel morphology at 90 days post-IR.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, positive data from animal studies used protocols with G-CSF administration before or at the time of infarct. [21][22][23][24] By comparison, in a study of immediate versus delayed (5 d postinfarct) G-CSF therapy, delayed therapy was associated with a 24% increase in end diastolic volume and a significant increase in infarct mass relative to placebo. 12 Similarly, a previous meta-analysis of clinical studies suggested benefit with early (< 37 h) initiation of G-CSF therapy.…”
Section: E432mentioning
confidence: 99%